Local parish of Our Lady of Bethlehem Church offering prayers - Mumbai Archive Project Team (Jio Institute, 2024)
Father Oscar Mendonca, dressed in a white cassock, leads the congregation in offering prayers and thanksgiving for a bountiful harvest. The occasion is marked by the lighting of candles and smashing of coconuts.